Chemistry of Essential Oils and Food Flavours (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint reviews a crop pest management use for several essential oils and the properties of an excellent lemon (citral) source. Research is reported on the biological properties of enhanced lemon oil along with the human intake of citrus beverages and the less common medicinal mastiha oil. Oils and hydrolates of rosemary and lavender were analyzed by headspace/GC-MS to better define their antibacterial, antioxidant and cytotoxic activities, and yeast particle encapsulation was investigated for the controlled release of bioactive terpenes.